2005
DOI: 10.1038/nature03715
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sensory deprivation prevents dendritic spine loss in primary somatosensory cortex

Abstract: A substantial decrease in the number of synapses occurs in the mammalian brain from the late postnatal period until the end of life. Although experience plays an important role in modifying synaptic connectivity, its effect on this nearly lifelong synapse loss remains unknown. Here we used transcranial two-photon microscopy to visualize postsynaptic dendritic spines in layer I of the barrel cortex in transgenic mice expressing yellow fluorescent protein. We show that in young adolescent mice, long-term sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
392
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 395 publications
(431 citation statements)
references
References 29 publications
29
392
3
Order By: Relevance
“…By setting a specific time window at postnatal week 3 in the initial analysis of the ASD mouse model, we aimed to detect any impairment in the regulatory mechanisms of spine remodelling. In this time window, spine density already reached the level of mature SSC, but active remodelling of spines still occurs, and both functional and structural plasticity is robust 25,31,32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By setting a specific time window at postnatal week 3 in the initial analysis of the ASD mouse model, we aimed to detect any impairment in the regulatory mechanisms of spine remodelling. In this time window, spine density already reached the level of mature SSC, but active remodelling of spines still occurs, and both functional and structural plasticity is robust 25,31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…1c). We performed in vivo two-photon imaging, mainly with a transcranial thinned-skull window, in this study 31,32 . In some experiments with young animals, we applied the open-skull technique 33 (refer to Methods for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that chessboard deprivation leads to rapid increase in both elimination and formation of dendritic spines in young adult mice. In another study, Zuo et al 40 found that similar to all-whisker trimming, chessboard trimming over two weeks preferentially reduces spine elimination without effect on spine formation in young adolescent mice. The effect of chessboard trimming, however, is less robust with all-whisker trimming.…”
Section: Experience-dependent Plasticity Of Dendritic Spinesmentioning
confidence: 99%
“…2,3,6 Recently, TPM has been used to examine the long-term effect of sensory experience on the rates of dendritic spine elimination and formation in mouse barrel cortex, a cortical region in which sensory input can be easily manipulated. By trimming all the whiskers on one side of the mouse facial pad daily, Zuo et al 40 showed that during the second postnatal month when extensive spine loss occurs, sensory deprivation preferentially reduces the rate of spine elimination but not formation. In contrast, no significant difference in spine elimination was found in adult mice over two weeks, suggesting that the impact of sensory deprivation on spine elimination diminishes as animals reach adulthood.…”
Section: Experience-dependent Plasticity Of Dendritic Spinesmentioning
confidence: 99%